2015
DOI: 10.3923/ja.2015.49.61
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Oil Palm Seedlings to the Drought Stress Using Boron and Silicon Applications

Abstract: A B S T R A C TThe objectives of the study were to determine (1) The level of physiological resistance of oil palm seedlings to drought stress by boron (B) and silicon (Si) application and (2) The mechanism of B and Si actions to induce physiological resistance of oil palm seedlings to drought stress. The B and Si were the elements capably inducing the internal resistance of plant tissues to drought stress, especially through physiological resistance mechanisms. Field trial was arranged in the factorial Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 36 publications
0
16
0
3
Order By: Relevance
“…Data are corroborated by the study of Gong et al (2005), which explained that Si has the ability to decrease transpiration via the cuticle or the stomata, due to its involvement in the regulation of the stomatal movement. These findings are also reinforced by the studies of Zargar and Agnihotri (2013), Putra et al (2015), and Zanetti et al (2016) in maize, oil palm, and cacao plants; they reported that Si application reduced the SD, an important factor to reduce gs, which improved the water status of plants under drought stress. Many studies have described how a minor SD is associated with the high PN and WUE in plants under drought stress conditions, as corroborated by us in our study (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Data are corroborated by the study of Gong et al (2005), which explained that Si has the ability to decrease transpiration via the cuticle or the stomata, due to its involvement in the regulation of the stomatal movement. These findings are also reinforced by the studies of Zargar and Agnihotri (2013), Putra et al (2015), and Zanetti et al (2016) in maize, oil palm, and cacao plants; they reported that Si application reduced the SD, an important factor to reduce gs, which improved the water status of plants under drought stress. Many studies have described how a minor SD is associated with the high PN and WUE in plants under drought stress conditions, as corroborated by us in our study (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies have shown that environmental stress leads to a change in stomatal density and size [ 63 – 67 ]. Supplying Si can change the stomatal density and size of a leaf to enhance the resistance of a plant [ 63 , 64 , 68 , 69 ]. Previous studies have shown that higher stomatal densities and smaller stomatal sizes improved the sensitivity of the stomatal regulation of the plants and improved the stomatal function at similar leaf areas.…”
Section: Discussionmentioning
confidence: 99%
“…increased in vegetative tissues in response to drought [30], while the total soluble protein content was affected by increasing drought severity [31]. Previous results showed that boron (B) and silicon (Si) application could induce physiological resistance of oil palm seedlings to drought stress [32]. The genes involved in cellular nitrogen compound metabolic processes and transmembrane transport are differentially expressed during drought treatments [33].…”
Section: Cold Stress Effects On the Expression Profiles Of Amino Acidmentioning
confidence: 99%